PENGARUH KUNJUNGAN WISATAWAN, PENDAPATAN PHR, DAN PENERIMAAN RETRIBUSI OBYEK WISATA TERHADAP PAD KABUPATEN GIANYAR - swantara, budi praga; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 12, Desember 2017 (pp. 2352 - 2582), 2017)
ABSTRACT Gianyar regency tourism sector is a potential sector to be developed as one source of local revenue. Gianyar regency provides hotels and restaurants as a means to support tourism as a source of lokal revenue through the mediation of tourism distribution so as to contribute to lokal revenues Gianyar regency . This study aims to determine how the influence of the tourist visits, Income trade sector of hotel restaurant and retribution tourism object to local revenue in Gianyar Regency. The data used in this research is secondary data, and the analytical technique used is path analysis technique (path analysis). The test results show the total of tourist visits and the income of the trade sector, hotels and restaurants affect the retribution of tourism in Gianyar regency. Visits of tourists and the receipt of the retribution tourist attraction does not affect the local revenue while the income of the trade sector hotels and restaurants affect the local revenue. In addition, there is an indirect influence of the tourist arrivals and trade sector revenues, Hotels and restaurants to the local revenue through the retribution of tourism objects or in other words the retribution tourism object is a variable of mediation in the influence of the  tourist visits revenues in trade sector, Hotels and restaurants to local revenue in Gianyar Regency.       Keywords: total of tourist visits, PHR sector revenue, levies tourism object, PAD